Neuronal circadian clock protein oscillations are similar in behaviourally rhythmic forager honeybees and in arrhythmic nurses - Fuchikawa, T. (Open Biol, 2017)
Internal clocks driving rhythms of about a day (circadian) are ubiquitous in animals, allowing them to anticipate environmental changes. Genetic or environmental disturbances to circadian clocks or the rhythms they produce are commonly associated with illness, compromised performance or reduced survival. Nevertheless, some animals including Arctic mammals, open sea fish and social insects such as honeybees are active around-the-clock with no apparent ill effects. The mechanisms allowing this remarkable natural plasticity are unknown. We generated and validated a new and specific antibody against the clock protein PERIOD of the honeybee Apis mellifera (amPER) and used it to characterize the circadian network in the honeybee brain. We found many similarities to Drosophila melanogaster and other insects, suggesting common anatomical organization principles in the insect clock that have not been appreciated before. Time course analyses revealed strong daily oscillations in amPER levels in foragers, which show circadian rhythms, and also in nurses that do not, although the latter have attenuated oscillations in brain mRNA clock gene levels. The oscillations in nurses show that activity can be uncoupled from the circadian network and support the hypothesis that a ticking circadian clock is essential even in around-the-clock active animals in a constant physical environment.